Hyperthyroidism and fulminant myocarditis in an adolescent with iodine-induced hyperthyroidism: A case report - Teng Fang Lai; ZhengJiang Liu (SAGE Open Medical Case Reports)
This paper describes the case of a 15-year-old male patient who exhibited chest distress and pain following an upper respiratory tract infection. Upon admission, the patient exhibited elevated levels of myocardial enzymes and troponin I. Electrocardiography revealed an acute inferior myocardial infarction. Coronary computed tomography angiography ruled out coronary stenosis; however, cardiac magnetic resonance imaging revealed myocardial congestion and edema. Subsequent examinations revealed increased thyroid hormone levels and decreased thyroid-stimulating hormone levels, which is consistent with the manifestations of hyperthyroidism. The patient was diagnosed with acute fulminant myocarditis accompanied by iodine-induced hyperthyroidism. The patient received no pharmacologic treatment for hyperthyroidism but was prescribed a low-iodine diet, medication, and supportive treatment. His myocardial enzymes and troponin I levels gradually decreased, his electrocardiography and echocardiography results improved, and his cardiac function returned to normal. The patient was discharged and advised to maintain a low-iodine diet. At the 6-month follow-up, the patient’s thyroid function and cardiac indicators had returned to normal. This case demonstrates that myocardial injury can result from myocarditis and iodine-induced hyperthyroidism and highlights the importance of closely monitoring and assessing thyroid function during treatment.